COVID-19 Challenges in Philippine Education: Paradigm Shifts and Opportunities - Marquez, Leander P.; Ombao, Rola P.; Brijuega, Chloe E.; Olivar, Marqz Verone V.; Cerio, Wulmar C.; Baes, Francisco D. (Diliman Review; Vol 64 No 1 (2020), 2024)
The COVID-19 pandemic caught most of the world unprepared. Deaths are in the thousands and cities are going into lockdowns. In a developing country such as the Philippines, one of the areas that is most affected by the onslaught of the virus is the education sector. Before the pandemic, the country had its hands full in its efforts to improve the quality of education and make sure that it is accessible to its citizens. While this endeavor has proven to be hard enough, the pandemic seems to have made everything worse. In this light, this paper will look into the impact of the COVID-19 pandemic in relation to challenges, paradigm shifts, and opportunities for education in the Philippine-setting. A proposal for learning by building communities of inquiry will be presented as a recommendation.